SOUND WAVE PROPAGATION AND REFLECTION BASED ON TRAM NOISE - ORYNCHAK, MARIIA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Sound wave propagation and reflection are critical phenomena that significantly impact urban environments, with tram noise being a prominent contributor. Understanding the intricacies of how sound waves propagate and reflect in the context of tram-related activities is vital for mitigating noise pollution and creating more sustainable and livable cities. This article explores the scientific and practical aspects of sound wave propagation and reflection, focusing on specifically tram-generated noise.Exploring the dynamics of sound wave propagation and reflection, this article delves into tram-generated noise within urban environments, specifically on paved surfaces. Focused on understanding the behavior of tram noise, it uncovers patterns influencing sound propagation. The aim is to provide insights for effective strategies to mitigate tram-related noise, bridging theory and practical applications for informed urban planning, based on experimentation and practical results.Urban soundscapes bear the unmistakable imprint of myriad features tied to tram-generated noise, particularly on different road surfaces and amidst varying rail setups and street widths. The exploration of noise reflection from diverse tram types assumes a crucial role in deciphering and alleviating the repercussions of urban transit on the acoustic ambiance.By pooling experimental data collected in real-world scenarios and amalgamating information from a spectrum of tram models in Lviv, distinct patterns and factors steering noise reflection become discernible. This amalgamation not only enriches our comprehension of noise dynamics but also forms the bedrock for devising more potent strategies in the realm of noise management.
Keywords: sound reflection; acoustic waves; sound propagation; tram sound propagation; tram-generated noise